Europa '94 : Junge europäische Kunst in München - Hypo-Kulturstiftung, München (München : Siemens, 1994)
Abad, Antoni ; Arcangeli, Maurizio ; Archipov, Vladimir ; Ballet, Elisabeth ; Besukladnikov, Andrej ; Birza, Rob ; Blanc, Jean-Luc ; Blaussyld, Maurice ; Bonde, Peter ; Bossu, Sylvia ; Brener, Alexander ; Bullacher, Gisela ; van Caeckenbergh, Patrick ; Colomer, Jordi ; Connor, Alan ; Dera, Cor ; etc.
Europa '94 : Junge europäische Kunst in München, 9. - 28. September 1994
boek
Keywords: Duitsland; München